Arahan Pengendalian Alih Pemanfaatan Lahan Pertanian Kawasan Perumahan Di Perkotaan Pangkajene (Studi Kasus Kelurahan Batu Lappa) - Ngaisah, Nurul; Syafri; Syam, Nur; Lakatupa, Gaffat (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study was to formulate directions for controlling land use change in residential areas in the Batulappa sub-district by identifying the factors that influence it. The research location is in BatuLappa Village, Watang Pulu District, Sidenreng Rappang Regency. This research was conducted using a quantitative and qualitative approach, first collecting primary data and then processing the primary data obtained with the results of an analysis through calculation so that the output obtained is in the form of predetermined numerical data. The primary data was obtained through observation and interviews by filling out questionnaires in the BatuLappa Village community and the calculation analysis was carried out through chi-square analysis so as to produce output which was described using a qualitative descriptive analysis method. From the results of the analysis of the chi-square factors that influence housing growth in the BatuLappa Village, namely culture which has a moderate effect, livelihoods has a weak effect, supervision has a moderate effect and the road network has a moderate effect. Where based on this variable, the references for the formulation of control directives were put together by reviewing several journals and regulations so that a formulation of directives for controlling the use of residential land in BatuLappa Village was issued.